Discourse Analysis and Humor on Papuan Mop in the Series of “Epen Kah Cupen Toh” - Aldrin Yohanes Ferdinandus; Ounu Zakiy Sukaton; Patrisius Istiarto Djiwandono (Hasanuddin University, 2023)
This study aims to explore the humor and discourse in Papuan MOP, as depicted in the 2010 YouTube video series